When is transition over? - Brown, Annette N., 1966-; Western Michigan University. Department of Economics; W.E. Upjohn Institute for Employment Research (Kalamazoo, MI : W.E. Upjohn Institute for Employment Research, 1999)
Contains six lectures which discuss criteria for determining the end of the transition process. These include changes in the characteristics of the economic system, outcomes of the transition process, and institutional reforms.
What is still missing? / by Marie Lavigne -- The end of transition? / by Alan Gelb -- The end of rent-seeking: the end of postcommunist transformation / by Anders Aslund -- China's unfinished economic transition / by Nicholas R. Lardy -- The transition is not over, but note the merits of the Central European model / by Jan Svejnar -- Reforming the welfare state in postsocialist economies / by Janos Kornai.
Essays based on six presentations given at the 33rd Annual Lecture-Seminar Series of the Dept. of Economics at Western Michigan University, held during the 1997-1998 academic year. The lecture series is cosponsored by the Department and the W.E. Upjohn Institute for Employment Research.
Includes bibliographical references and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
Keywords: Post-communism -- Europe, Eastern -- Congresses; Capitalism -- Europe, Eastern -- Congresses; Post-communism -- Economic aspects -- Europe, Eastern -- Congresses; Mixed economy -- China -- Congresses; China -- Economic conditions -- 1976-2000 -- Congresses; China -- Economic policy -- 1976-2000 -- Congresses; China -- Politics and government -- 1976- -- Congresses; Capitalism -- Europe, Eastern -- Congresses; Post-communism -- Economic aspects -- Europe, Eastern -- Congresses; Mixed economy -- China -- Congresses; Post-communism -- Europe, Eastern -- Congresses; China -- Economic conditions -- 1976-2000 -- Congresses; Économie de marché -- Europe de l'Est -- Congrès.; Postcommunisme -- Aspect économique -- Europe de l'Est -- Congrès.; Économie mixte -- Chine -- Congrès.; Postcommunisme -- Europe de l'Est -- Congrès.; Chine -- Conditions économiques -- 1976-2000 -- Congrès.; Chine -- Politique économique -- 1976- -- Congrès.; Chine -- Politique et gouvernement -- 1976- -- Congrès.; Postcommunisme -- Europe de l'Est -- Congrès.; Postcommunisme -- Aspect économique -- Europe de l'Est -- Congrès.; Économie mixte -- Chine -- Congrès.; Chine -- Conditions économiques -- 1976-2000 -- Congrès.; Chine -- Politique économique -- 1976-2000 -- Congrès.; BUSINESS & ECONOMICS -- Free Enterprise; Capitalism; Economic history; Economic policy; Mixed economy; Politics and government; Post-communism; Post-communism -- Economic aspects; China; Eastern Europe; Wirtschaftssystem; Aufsatzsammlung; Osteuropa; Economische hervormingen; Economische situatie; economic reform; structural change; market economy; economic policy; foreign investment; stabilization; inflation; EU; membership; privatization; price policy; corruption; banking; mixed economy; human capital; unemployment; social protection; medical care; financing; taxation; statistical table